2013
DOI: 10.7861/clinmedicine.13-4-383
|View full text |Cite
|
Sign up to set email alerts
|

Conservative care for end-stage kidney disease: joint medical conference with the Renal Association, British Geriatrics Society and Association for Palliative Medicine

Abstract: -Conservative care is one of the fastest-changing areas of renal medicine. Non-dialytic therapy is now established as a treatment option in most renal units in the UK. This conference reviewed the history of conservative management and examined the state of current practice. The challenges now faced include expanding the evidence base in this area, improving the information given to patients and their families to help them make a decision about treatment, and responding to changes in NHS funding to ensure cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 8 publications
0
13
0
2
Order By: Relevance
“…Their data were, however, published in 2005 and in 2006, and since then CKM has been established as a treatment option in many UK renal units. CKM is one of the fastest-changing areas of renal medicine, 58 and there is a need to understand how it is delivered nationally.…”
Section: Discussionmentioning
confidence: 99%
“…Their data were, however, published in 2005 and in 2006, and since then CKM has been established as a treatment option in many UK renal units. CKM is one of the fastest-changing areas of renal medicine, 58 and there is a need to understand how it is delivered nationally.…”
Section: Discussionmentioning
confidence: 99%
“…Conservative care for ESRD is evolving in the UK (19), and information on how it is practiced is limited to individual units. In 2005, Gunda et al (20) reported significant variation in the provision of palliative care for ESRD across the UK.…”
Section: Introductionmentioning
confidence: 99%
“…Bei schlechten Erfolgsaussichten sollte im Vordergrund stehen, den Patienten vor weiterem Schaden zu bewahren. Hinweise für eine strukturierte Evaluation der mit dem ANV verknüpf-tem Problem einer gemeinsamen Entscheidungsfindung liegen vor [12,36,37]. Für Patienten, die nicht entscheidungsfähig sind und bei denen keine Willensäußerung vorliegt und eine gesetzliche Betreuung angeregt wurde, gelten besondere Rechte bezüglich der Entscheidungsfindung [38].…”
Section: Therapeutische üBerlegungenunclassified
“…den "konservativen" Therapieansatzes fortzusetzen, muss in Erwägung gezogen werden. Dieser Aspekt gewinnt mit der Alterung der Gesellschaft zunehmend an Bedeutung[36]. decision making | Die Lebenserwartung älterer Dialysepatienten ist begrenzt und Folgeerkrankungen sowie die chronische Dialysebehandlung beeinträchtigen die Lebensqualität.…”
unclassified